Proceso Financiero De La Empresa “Decosind S.A.” - Barriga Haz, Kenya Denisse (2018)
This study presents an analysis of the financial process carried out by the company Decosind S.A., not only to determine the current situation in which it is located, but also because it helps us to know what the company's future evolution will be The financial process is essential for the economic-financial management of a company whose purpose is to improve and optimize the company, this is one of the most effective processes for the subsistence and growth of the company, through compliance with the phases of the financial process which are planning, execution and analysis and control and decision making about the state of the company. Financial planning in companies helps them to elaborate in an integrated, organized and personalized way their proposed objectives so that each of them can be optimally fulfilled. By having a relevant internal control within the company, the management of human, technical and financial resources is improved, the latter being the most aggravating factor in the company. The objective of this case study is to analyze the financial ENTERPRISE DECOSIND SA PROCESS, applying the method of explanation and documentary under the sub line of research management accounting information, for which we resorted to the use of documents on websites, books , interviews to the accountant, scientific articles and pertinent laws, the same that were guides for the detection of the problems that are being raised, causing an unstable administrative and financial situation in the company. Inf